Kontribusi Ilmu Fonetik Dalam Studi Bahasa Arab - Masyhur Dungcik Senen (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2017)
This description will depict how and what in fact that Ianguage. Ianguage basically a sign owning meaning based on agreement of user/ wearer,where that sign in the form of sound which”sometime realized into letter form. structured systematically and sistemis. Ianguage used human being as a means of unruk work along, communicating, identifying x'self and various other function, pursuant to whom, what, to whom, about whom, where, when, old to what end and with what that Ianguage [is] said. Its nucleus;core, the happening of Ianguage caused by sound Keyword : Fonetik , Fonemik, Komunikasi, Bahasa Arab.